Functionalized polyolefin-based nanoparticles as well as preparation method and application thereof
By preparing functionalized polyolefin-based nanoparticles with core-shell structures in the polyolefin matrix, the problem of poor compatibility between the polyolefin matrix and functional additives is solved, the uniform distribution of the additives and the improvement of material properties is achieved, and the flame retardant and antioxidant effects are good.
Patent Information
- Application Number
- CN202411796203.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Due to its non-polar properties and low surface energy, the polyolefin matrix resin has poor compatibility with functional additives, which leads to the additives being unable to be uniformly distributed in the material and easily migrate, affecting material performance and environmental safety.
Functionalized polyolefin-based nanoparticles with core-shell structures are used, and their core layer contains functional groups such as flame retardant groups and antioxidant groups. The shell layer is a polyolefin chain with stable effects. It is prepared by polymerization-induced self-assembly technology to ensure the stability of the morphology of the nanoparticles and the uniform distribution of functional additives.
It improves the compatibility of the polyolefin matrix with functional additives, reduces the migration of additives, enhances the flame retardant and antioxidant properties of the material, extends the service life of the material, and reduces the risk of environmental pollution.
Smart Images

Figure CN119751768A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to functionalized polyolefin-based nanoparticles and a preparation method and application thereof. Background Art
[0002] Polyolefins have attracted wide attention due to their excellent performance, chemical stability, easy processing, cost-effectiveness and diverse applications. Polyolefins meet many of our daily needs, occupying more than 60% of the market share and being the most widely used type of polymer. In the actual application of polyolefin products, it is often necessary to add a variety of additives such as plasticizers, antioxidants, light stabilizers, antistatic agents, etc. to improve the weather resistance, processability, mechanical properties, etc. of the products.
[0003] However, due to its non-polar properties and low surface energy, the compatibility between polyolefin matrix resin and functional additives is often poor. This compatibility difference leads to phase separation inside the material, and the additive cannot be evenly distributed in the polymer matrix, forming microphase or aggregate regions. Furthermore, the functional additive is easy to migrate to the surface of the material or the external environment. On the one hand, migration reduces the effectiveness of the functional additive in the matrix and causes the comprehensive performance of the material to decline. On the other hand, migration causes surface contamination of the material, resulting in surface stickiness, frosting, whitening, etc., affecting the appearance and touch of the material, and even affecting the secondary processing performance of the material. Furthermore, migration can also cause environmental and health problems. The migration and release of additives may cause environmental pollution or have adverse effects on human health, especially some toxic or harmful additives. To improve compatibility and reduce the migration of functional additives, the following measures can usually be taken: (1) Select additives with better compatibility to reduce the possibility of phase separation and migration. (2) Surface treatment of the polyolefin matrix or blending modification with other polymers with better compatibility to improve the compatibility between the matrix and the additive. (3) Introducing cross-linked structures or forming physical networks in the polyolefin matrix to limit the migration of additives. (4) Using nanoparticles with both polyolefin chains and functional chains as functional additives, taking advantage of the excellent compatibility between the polyolefin chains and the matrix resin, the purpose of reducing migration can be achieved. By rationally selecting additives, modifying the matrix resin, and introducing new material technologies, this problem can be alleviated to a certain extent, extending the service life of the material and maintaining the stability of its performance. However, these methods still have various limitations and problems to a certain extent. Among them, polyolefin-based nanoparticle functional additives improve compatibility by optimizing the interaction between polyolefin and functional additive components at the nanoscale, thereby improving the overall material performance; compared with other methods, the method of using polyolefin-based nanoparticle functional additives shows many advantages and important application potential.
[0004] In the past two decades, polymer self-assembly technology has provided a new method for the preparation of nanoparticles and significantly promoted its application. The self-assembly system in solution has developed from the traditional dilute solution self-assembly (<1.0% w / w) to the polymerization-induced self-assembly technology with high solid content (up to 50% w / w). Nevertheless, due to the complex stereoregular structure and special dissolution behavior of traditional polyolefins such as polyethylene and polypropylene, as well as the high difficulty in synthesizing topological polymers containing polyolefin chains, research in this field has been limited to a certain extent, resulting in the current polymerization-induced self-assembly mostly focusing on poly(meth)acrylates, polystyrenes, polycaprolactone polymers, etc. For polyolefin polymers, most solution self-assembly research focuses on crystallization-driven self-assembly with polyolefin as the core. For example, Schmalz et al. demonstrated that the triblock copolymer polystyrene-b-polyethylene-b-polymethyl methacrylate can form spherical crystal core micelles in toluene and worm-like micelles in dioxane through crystallization-driven self-assembly (ACS Nano, 2011, 5(12): 9523-9534.). They also dissolved polystyrene-b-polyethylene-b-polystyrene in xylene to obtain spherical seed micelles, which were then converted into triblock micelles through controlled crystallization-driven self-assembly (Journal of the American Chemical Society, 2012, 134(34): 14217-14225.) However, the preparation and application of nanoparticles with polyolefin shells are still relatively rare.
[0005] In summary, based on the problems and defects of the existing technology, it is necessary to propose a method for efficiently preparing functionalized polyolefin-based nanoparticles and develop its application research. Summary of the invention
[0006] The purpose of the present invention is to provide a functionalized polyolefin-based nanoparticle and a preparation method and application thereof in order to solve at least one of the above problems, so as to solve the defects of the prior art such as poor compatibility of functional additives with polyolefin matrices, easy migration of functional additives and insufficient functionality of polyolefins leading to application limitations. This scheme provides a nanoparticle with a polyolefin shell, which has good controllability and has potential application prospects in the fields of flame retardants, antioxidants, etc.; and the preparation method of the nanoparticle is simple, efficient and universal.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] The first aspect of the present invention discloses a functionalized polyolefin-based nanoparticle, wherein the nanoparticle is a core-shell structure, wherein the core layer is a polymer containing functional groups, and the shell layer is a polyolefin chain with a stabilizing effect. The functional groups contained in the core layer include flame retardant groups, antioxidant groups, etc.
[0009] Preferably, the polymer containing functional groups is a polymer chain containing epoxy groups that is post-modified with functional groups;
[0010] The functional groups include one or more combinations of phosphate, hindered amine, hindered phenol and 2,2,6,6-tetramethylpiperidinyl oxide.
[0011] Preferably, the polyolefin chain comprises one or more combinations of hydrogenated polydienes, hydrogenated polycycloolefins, polyisobutylene, polyethylene and polypropylene.
[0012] The second aspect of the present invention discloses a method for preparing the functionalized polyolefin-based nanoparticles as described above, comprising the following steps:
[0013] S1: Polyolefin-based macromolecular initiator, small molecule initiator, epoxy group-containing monomer and catalyst are subjected to atom transfer radical polymerization-mediated polymerization-induced self-assembly in a solvent to prepare a nanoparticle precursor having a core layer of epoxy group-containing polymer chains and a shell layer of a stabilizing polyolefin chain;
[0014] S2: adding a functional additive to the nanoparticle precursor obtained in step S1, and reacting to obtain functionalized polyolefin-based nanoparticles having a core layer of a polymer containing functional groups and a shell layer of a polyolefin chain having a stabilizing effect.
[0015] Preferably, the polyolefin-based macroinitiator is prepared by the following steps:
[0016] SS1: Preparation of hydroxyl-terminated precursors by controlled polymerization and end-capping of olefin monomers, and preparation of hydroxyl-terminated polyolefin polymers by hydrogenation;
[0017] SS2: The hydroxy-terminated polyolefin polymer obtained in step SS1 is subjected to an esterification reaction with a bromine-containing small molecule reagent to obtain a polyolefin-based macromolecular initiator containing terminal bromine.
[0018] Preferably, step SS1 includes one or both of the following:
[0019] i) the controlled polymerization comprises one or more combinations of anionic polymerization, coordination polymerization and ring-opening metathesis polymerization;
[0020] ii) The catalyst for the hydrogenation reaction comprises a combination of one or more of p-toluenesulfonyl hydrazide, lead / barium sulfate, nickel / aluminum catalyst and platinum / rhenium catalyst.
[0021] Preferably, in step SS2, the bromine-containing small molecule reagent includes one or a combination of 2-bromoisobutyryl bromide and α-bromophenylacetic acid.
[0022] Preferably, step S1 includes one or more of the following:
[0023] i) the small molecule initiator comprises one or a combination of ethyl 2-bromo-2-methylpropionate and ethyl α-bromophenylacetate;
[0024] ii) the catalyst comprises one or more combinations of cupric bromide / tris(2-dimethylaminoethyl)amine / stannous octoate, cupric bromide / N,N,N',N",N"-pentamethyldiethylenetriamine, cupric bromide / tris(2-dimethylaminoethyl)amine / azobisisobutyronitrile and cupric bromide / tris(2-pyridylmethyl)amine / stannous octoate;
[0025] iii) the epoxy group-containing monomer comprises one or a combination of glycidyl methacrylate and glycidyl acrylate;
[0026] iv) the solvent is a good solvent for the polyolefin-based macromolecular initiator and a poor solvent for the polymer chain containing epoxy groups;
[0027] v) The reaction temperature of the atom transfer free radical polymerization-mediated polymerization-induced self-assembly is 25-150° C., the reaction time is 0.5-48 hours, and the solid content of the reaction system is 0.1-30%.
[0028] Preferably, in step S2, the functional additive includes a combination of one or more of phosphoric acid, phosphorus oxychloride, N-phenyl-p-phenylenediamine, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid and 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical.
[0029] The third aspect of the present invention discloses a use of any of the above-mentioned functionalized polyolefin-based nanoparticles in the field of flame retardants and antioxidants.
[0030] The working principle of the present invention is:
[0031] In this scheme, first, a variety of unsaturated polyolefin chains of different compositions, molecular weights, and topological structures are prepared by a controlled polymerization method, and a terminal hydroxyl precursor is prepared by end-capping. Then, it is hydrogenated, and a small molecule reagent is used to carry out an esterification reaction to prepare a polyolefin-based macromolecular initiator containing terminal bromine. Subsequently, the prepared macromolecular initiator and small molecule initiator, monomer containing epoxy groups, catalyst and solvent are subjected to a polymerization-induced self-assembly process mediated by atom transfer free radical polymerization to prepare nanoparticles with a core layer containing epoxy group polymer and a shell layer of a polyolefin chain with a stabilizing effect. Finally, a functional additive is added, and a functionalized polyolefin-based nanoparticle with a core of a polymer containing a functional group and a shell of a polyolefin chain with a stabilizing effect is prepared by a ring-opening reaction of an epoxy group.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The composition of the shell polymer, the core polymer and the core functional additive of the functionalized polyolefin-based nanoparticles prepared by the present invention is controllable; the preparation method provided by the present invention has the advantages of controllable functional groups, controllable assembly particle size, stable in-situ cross-linking of the assembly, simple operation, strong versatility, strong compatibility with polyolefin matrix resins, and a wide range of applications; the nanoparticles prepared by the present invention have potential application prospects in the fields of flame retardants, antioxidants, etc.
[0034] 1) The method for preparing functionalized polyolefin-based nanoparticles proposed in the present invention obtains in-situ cross-linked and stable nanoparticles by a polymerization-induced self-assembly method. Such a cross-linked structure ensures that the nanoparticles can maintain a stable morphology in the subsequent reaction with a functional additive.
[0035] 2) The method for preparing functionalized polyolefin-based nanoparticles proposed in the present invention has the advantages of controllable particle size of the assembly and adjustable functional groups in the core.
[0036] 3) The functionalized polyolefin-based nanoparticles proposed in the present invention are expected to be used in the fields of flame retardants, antioxidants, etc., and have industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a transmission electron microscope (TEM) image of the hydrogenated polyisoprene-b-polyglycidyl methacrylate / polyglycidyl methacrylate polyolefin-based nanoparticles prepared in Example 1. The average size of the nanoparticles is 295 nm.
[0038] Figure 2 This is a transmission electron microscope (TEM) image of phosphoric acid@(hydrogenated polyisoprene-b-polyglycidyl methacrylate / polyglycidyl methacrylate) functionalized polyolefin-based nanoparticles prepared in Example 1. The average size of the nanoparticles is 341 nm.
[0039] Figure 3 This is a flame retardant property (heat release rate) test curve of the phosphoric acid @ (hydrogenated polyisoprene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate)) functionalized polyolefin-based nanoparticles prepared in Example 1 in Test Example 1.
[0040] Figure 4 This is a flame retardant property (heat release rate) test curve of the phosphoric acid @ (hydrogenated polyisoprene-b-polyglycidyl methacrylate) functionalized polyolefin-based nanoparticles prepared in Example 2 in Test Example 2. DETAILED DESCRIPTION
[0041] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0042] In the following description, unless otherwise specified, the reagents used are conventional commercially available products, and the methods used are common knowledge in the art.
[0043] In order to solve the defects of the prior art such as poor compatibility of functional additives with polyolefin matrices, easy migration of functional additives and application limitations caused by insufficient functionality of polyolefins, this scheme develops a simple, efficient and universal polymer and polyolefin-based nanoparticles with adjustable particle size containing functional groups in the core and a preparation method thereof.
[0044] Specific:
[0045] The invention discloses a functionalized polyolefin-based nanoparticle, which has a core-shell structure, wherein the core is a polymer chain containing a functional group, and the shell is a polyolefin chain having a stabilizing effect.
[0046] Preferably, the core of the functionalized polyolefin-based nanoparticles is obtained by epoxy ring-opening modification of a polymer chain containing epoxy groups; the functional groups include one or more combinations of phosphates, hindered amines, and hindered phenols; the stabilizing polyolefin chains include one or more combinations of hydrogenated polydienes (such as polyisoprene, polybutadiene, etc.), hydrogenated polycycloolefins (such as polycyclooctene, polycyclooctadiene, etc.), polyisobutylene, polyethylene, and polypropylene.
[0047] A method for preparing the functionalized polyolefin-based nanoparticles as described above comprises the following steps:
[0048] S1: preparing a hydroxyl-terminated precursor by controlled polymerization and end-capping reaction of olefin monomers, and preparing a hydroxyl-terminated polyolefin polymer by hydrogenation reaction;
[0049] S2: using the esterification reaction of terminal hydroxyl polyolefin polymer and small molecule reagent to prepare a polyolefin-based macromolecular initiator for atom transfer radical polymerization containing terminal bromine;
[0050] S3: subjecting the polyolefin-based macromolecular initiator, small molecule initiator, epoxy-containing monomer, catalyst and solvent obtained in step S1 to a polymerization-induced self-assembly process mediated by atom transfer radical polymerization to prepare block polymers and nanoparticles having a core layer of epoxy-containing polymer and a shell layer of a stabilizing polyolefin chain;
[0051] S4: adding a functional additive to the nanoparticles obtained in step S3 to react with epoxy groups to prepare functionalized polyolefin-based nanoparticles having a core of a polymer containing functional groups and a shell of a polyolefin chain having a stabilizing effect.
[0052] In the present invention, a polyolefin-based macromolecular initiator is used, and a small molecule initiator is added at the same time to realize the controllable preparation of nanoparticles with adjustable particle size through polymerization-induced self-assembly technology, and further through the ring-opening reaction of epoxy groups, nanoparticles with a core of a polymer containing a functional group and a shell of a polyolefin chain with a stabilizing effect are prepared. This is a new method for efficiently preparing functionalized polyolefin-based nanoparticles, and is also the key to the present technical solution.
[0053] More preferably, the hydrogenation reaction is selected from a combination of one or more of p-toluenesulfonyl hydrazide hydrogenation, hydrogenation using lead / barium sulfate as a catalyst, hydrogenation using a nickel / aluminum catalyst, and hydrogenation using a platinum / rhenium catalyst.
[0054] More preferably, the polydienes are selected from polyisoprene, poly 1,3-butadiene, poly 1,3-pentadiene, poly 1,4-pentadiene, poly 1,3-hexadiene, poly 1,4-hexadiene, poly 1,5-hexadiene, poly 2-methyl-1,3-pentadiene and the like.
[0055] More preferably, the polycycloolefins are selected from polycyclooctadiene, polycyclopentadiene, polycyclooctene, polycyclopentene and the like.
[0056] Preferably, in step S1, the controllable polymerization reaction includes a combination of one or more polymerization methods selected from the group consisting of living anionic polymerization, coordination polymerization, and ring-opening metathesis polymerization.
[0057] Preferably, in step S2, the small molecule reagent comprises one or a combination of 2-bromoisobutyryl bromide or α-bromophenylacetic acid.
[0058] Preferably, in step S3, the small molecule initiator comprises one or a combination of ethyl 2-bromo-2-methylpropionate and ethyl α-bromophenylacetate.
[0059] Preferably, in step S3, the catalyst includes one or more combinations of cupric bromide / tris(2-dimethylaminoethyl)amine / stannous octoate, cupric bromide / N,N,N',N",N"-pentamethyldiethylenetriamine, cupric bromide / tris(2-dimethylaminoethyl)amine / azobisisobutyronitrile, and cupric bromide / tris(2-pyridylmethyl)amine / stannous octoate.
[0060] Preferably, in step S3, the solvent is a good solvent for the macromolecular initiator and a poor solvent for the polymer chain containing epoxy groups.
[0061] More preferably, the solvent includes one or more combinations of toluene, cyclohexane, and n-heptane.
[0062] Preferably, in step S3, the epoxy group-containing nucleating chain monomer includes a combination of one or more monomers selected from glycidyl methacrylate and glycidyl acrylate.
[0063] Preferably, in step S3, the atom transfer radical polymerization-mediated polymerization-induced self-assembly process includes one or more combinations of a conventional atom transfer radical polymerization-mediated polymerization-induced self-assembly process, an electron transfer-regenerated catalyst atom transfer radical polymerization-mediated polymerization-induced self-assembly process, an initiator-continuously-regenerated catalyst atom transfer radical polymerization-mediated polymerization-induced self-assembly process, a zero-valent copper-catalyzed atom transfer radical polymerization-mediated polymerization-induced self-assembly process, and an electrically-regulated and light-induced atom transfer radical polymerization-mediated polymerization-induced self-assembly process.
[0064] Further preferably, in step S3, the atom transfer radical polymerization-mediated polymerization-induced self-assembly process includes a conventional atom transfer radical polymerization-mediated polymerization-induced self-assembly process, an electron transfer-regenerated catalyst atom transfer radical polymerization-mediated polymerization-induced self-assembly process, and an initiator-continuously-regenerated catalyst atom transfer radical polymerization-mediated polymerization-induced self-assembly process.
[0065] Preferably, in step S3, the reaction temperature of the atom transfer radical polymerization is 25-150° C., the reaction time is 0.5-48 h, and the solid content of the reaction system is 0.1-30%.
[0066] Further preferably, in step S3, the reaction temperature of the atom transfer radical polymerization is 25-75° C., the reaction time is 8-24 h, and the solid content of the reaction system is 1-30%.
[0067] Preferably, in step S4, the functional additive includes one or more combinations of phosphoric acid, phosphorus oxychloride, N-phenyl-p-phenylenediamine, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, and 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical.
[0068] The functionalized polyolefin-based nanoparticle shell as described above is used in flame retardants and antioxidants.
[0069] Example 1
[0070] This example is the preparation of phosphoric acid@(hydrogenated polyisoprene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles:
[0071] (1) Preparation of hydrogenated polyisoprene-bromine macroinitiator
[0072] The hydroxy-terminated polyisoprene was synthesized by living anionic polymerization. First, dry cyclohexane (215 mL, 169 g) and isoprene (44 mL, 30.06 g) were introduced into a 500 mL pre-baked vacuum-sealed flask filled with nitrogen. Then, the impurities in the mixture were consumed by adding sec-butyl lithium, and the measured sec-butyl lithium (6.70 mL, 6.03 mmol) was quickly added to initiate the polymerization; after 24 hours, 0.4 mL of the mixture was taken out for characterization. Subsequently, propylene oxide (5.00 mL, 4.15 g) previously removed by n-butyl lithium was added, the reaction was continued for 24 hours, and acidic methanol (0.10 mL) was added to terminate the reaction. Finally, the hydroxy-terminated polyisoprene was purified by precipitation in methanol three times and dried in a vacuum oven for further experiments. The number average molecular weight M was measured by gel permeation chromatography (GPC). n =7,000 g / mol, M w / M n =1.05; using nuclear magnetic resonance spectroscopy ( 1 HNMR) measured the monomer conversion rate to be >99%.
[0073] Hydrogenated polyisoprene with terminal hydroxyl groups was synthesized by hydrogenation reaction. First, the polyisoprene with terminal hydroxyl groups (9.40 g, 1.34 mmol) was dissolved in p-xylene (62 mL, 53.30 g), and p-toluenesulfonyl hydrazide (5.14 g, 27.60 mmol) was added. Then, after heating to reflux at 135°C for 15 minutes, p-toluenesulfonyl hydrazide (a total of 102.80 g) was added in 20 batches at intervals of 15 minutes. After the last addition of p-toluenesulfonyl hydrazide, the mixture was heated to reflux for another 30 minutes. Finally, a mixed solution of sodium hydroxide in methanol and water (pH = 11) was used as a precipitant, and precipitated three times therein to purify and recover the hydrogenated polyisoprene with terminal hydroxyl groups, and then dried in a vacuum oven for the next step of the experiment. The number average molecular weight M was measured by gel permeation chromatography (GPC). n =7,600 g / mol, M w / M n =1.06; using nuclear magnetic resonance spectroscopy ( 1 H NMR) showed that the hydrogenation rate was >99%.
[0074] Hydrogenated polyisoprene-bromine macroinitiator was synthesized by esterification reaction. First, the hydrogenated polyisoprene (11.60 g, 1.53 mmol) of terminal hydroxyl group was dissolved in toluene (250 mL, 216.50 g) and distilled at 140 ° C to remove trace water by azeotropic process. After the distillation process, triethylamine (4.60 mL, 3.35 g) and dry dichloromethane (210 mL, 278.38 g) were added. Subsequently, 2-bromoisobutyryl bromide (2.30 mL, 4.28 g) was added dropwise under an ice-water bath. After the addition was completed, the reaction continued at room temperature for 72 hours. Finally, the hydrogenated polyisoprene-bromine macroinitiator was purified by precipitation in methanol three times, dried in a vacuum oven, and stored in a refrigerator below 4 ° C for further experiments. The number average molecular weight M was measured by gel permeation chromatography (GPC). n =8,600 g / mol, M w / M n =1.06.
[0075] (2) Preparation of Hydrogenated Polyisoprene-b-Poly(Glycidyl Methacrylate) / Poly(Glycidyl Methacrylate) Polyolefin-Based Nanoparticles
[0076] First, hydrogenated polyisoprene-bromine macroinitiator (0.5000 g, 0.0581 mmol), ethyl 2-bromo-2-methylpropionate (0.0113 g, 0.0581 mmol), glycidyl methacrylate (0.6612 g, 4.6512 mmol), copper bromide (0.0010 g, 0.0046 mmol), tris[2-(dimethylamino)ethyl]amine (0.0021 g, 0.0093 mmol) and cyclohexane (4.6448 g) were added to a 10 mL flask in sequence. After bubbling with nitrogen for 30 minutes, the flask was placed in an oil bath at 60 ° C for 15 minutes. Then, stannous octoate (0.0377 g, 0.0930 mmol) dissolved in cyclohexane was added by a syringe to initiate polymerization. The polymerization reaction lasted for 24 hours to form a dispersion of spherical nanoparticles, realizing the polymerization-induced self-assembly process. The nanoparticles were precipitated in methanol three times before use. 1 H NMR) measured the monomer conversion rate> 99%; dynamic light scattering (DLS) and transmission electron microscopy (TEM) measured its average diameter of about 295nm, such as Figure 1 shown.
[0077] (3) Preparation of Phosphoric Acid@(Hydrogenated Polyisoprene-b-Poly(Glycidyl Methacrylate) / Poly(Glycidyl Methacrylate) Functionalized Polyolefin-Based Nanoparticles
[0078] First, the nanoparticles (0.5000 g) prepared above were redispersed in tetrahydrofuran (10.6 mL, 9.5 g), and phosphoric acid (0.30 mL) was added. Then, after heating under reflux at 90°C for 8 hours, phosphoric acid @ (hydrogenated polyisoprene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate)) functionalized polyolefin-based nanoparticles were prepared. Finally, the nanoparticles were precipitated in methanol three times to remove excess phosphoric acid. The nanoparticles were spherical in structure, and their average diameter was measured to be about 341 nm using dynamic light scattering (DLS) and transmission electron microscopy (TEM), as shown in FIG. Figure 2 shown.
[0079] Example 2
[0080] This example is the preparation of phosphoric acid @ (hydrogenated polyisoprene-b-poly(glycidyl methacrylate)) functionalized polyolefin-based nanoparticles:
[0081] (1) Preparation of hydrogenated polyisoprene-bromine macroinitiator
[0082] Same as Example 1(1).
[0083] (2) Preparation of Hydrogenated Polyisoprene-b-Poly(Glycidyl Methacrylate) Polyolefin-Based Nanoparticles
[0084] First, hydrogenated polyisoprene-bromine macroinitiator (0.5000 g, 0.0581 mmol), glycidyl methacrylate (2.6446 g, 18.6046 mmol), copper bromide (0.0042 g, 0.0186 mmol), tri[2-(dimethylamino)ethyl]amine (0.0086 g, 0.0372 mmol) and cyclohexane (16.1262 g) were added to a 10 mL flask in sequence. After bubbling with nitrogen for 30 minutes, the flask was placed in an oil bath at 60°C for 15 minutes. Then, stannous octoate (0.1507 g, 0.3721 mmol) dissolved in cyclohexane was added via a syringe to initiate polymerization. The polymerization reaction lasted for 24 hours to form a dispersion of spherical nanoparticles, realizing a polymerization-induced self-assembly process. The nanoparticles were precipitated in methanol three times for later use. The results were analyzed by nuclear magnetic resonance spectroscopy ( 1 The monomer conversion was >99% as measured by H NMR, and the products were characterized by dynamic light scattering (DLS) and transmission electron microscopy (TEM).
[0085] (3) Preparation of Phosphoric Acid @ (Hydrogenated Polyisoprene-b-Poly(Glycidyl Methacrylate)) Functionalized Polyolefin-Based Nanoparticles
[0086] First, the nanoparticles (0.5000 g) prepared above were redispersed in tetrahydrofuran (10.6 mL, 9.5 g), and phosphoric acid (1.20 mL) was added. Then, after heating under reflux at 90 ° C for 8 hours, phosphoric acid @ (hydrogenated polyisoprene-b-polymethacrylate glycidyl ester) functionalized polyolefin-based nanoparticles were prepared. Finally, the nanoparticles were precipitated in methanol three times to remove excess phosphoric acid. The nanoparticles were spherical in structure and were characterized by dynamic light scattering (DLS) and transmission electron microscopy (TEM).
[0087] Example 3
[0088] This example is the preparation of N-phenyl-p-phenylenediamine@(hydrogenated polyisoprene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles:
[0089] The phosphoric acid in Example 1 (3) is replaced with N-phenyl-p-phenylenediamine, the amount of tetrahydrofuran is increased by 1 time, the heating temperature is reduced to 40°C, the reaction time is increased to 24 hours, and the other steps are the same as Example 1, so as to prepare N-phenyl-p-phenylenediamine@(hydrogenated polyisoprene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles.
[0090] Example 4
[0091] This example is the preparation of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid@(hydrogenated polyisoprene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles:
[0092] The phosphoric acid in Example 1 (3) is replaced with 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, the amount of tetrahydrofuran is increased by 1 time, the heating reflux time is increased to 16 hours, and the other steps are the same as Example 1, so as to prepare 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid @ (hydrogenated polyisoprene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles.
[0093] Example 5
[0094] This example is the preparation of phosphoric acid @ (hydrogenated polybutadiene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles:
[0095] The isoprene in Example 1 (1) is replaced by butadiene, and the other steps are the same as Example 1, so as to prepare phosphoric acid @ (hydrogenated polybutadiene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles.
[0096] Example 6
[0097] This example is the preparation of N-phenyl-p-phenylenediamine@(hydrogenated polybutadiene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles:
[0098] The phosphoric acid in Example 5 is replaced with N-phenyl-p-phenylenediamine, the amount of tetrahydrofuran is increased by 1 time, the heating temperature is reduced to 40° C., the reaction time is increased to 24 hours, and the other steps are the same as Example 5, so as to prepare N-phenyl-p-phenylenediamine@(hydrogenated polybutadiene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles.
[0099] Example 7
[0100] This example is the preparation of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid@(hydrogenated polybutadiene-b-poly(glycidyl methacrylate / poly(glycidyl methacrylate)) functionalized polyolefin-based nanoparticles:
[0101] The phosphoric acid in Example 5 is replaced with 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, the amount of tetrahydrofuran is increased by 1 time, the heating reflux time is increased to 16 hours, and the other steps are the same as Example 5, so as to prepare 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid@(hydrogenated polybutadiene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate) functionalized polyolefin-based nanoparticles.
[0102] Example 8
[0103] This example is the preparation of 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical @ (polyethylene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles:
[0104] (1) Preparation of polyethylene macroinitiator
[0105] Through coordination polymerization, a catalytic system of bis[N-(3-tert-butyl salicylaldehyde) cyclopentylamine] zirconium dichloride as the main catalyst and methylaluminoxane as the co-catalyst was used to synthesize polyethylene with terminal double bonds in toluene. First, toluene (500mL) was added to a 1L flask that was pre-evacuated and nitrogen-filled. Deionized water (0.23g, 0.013mol) and trimethylaluminum (20.00mL, 0.020mol) were added in sequence and stirred for 2 hours. Deionized water and trimethylaluminum reacted to produce the co-catalyst methylaluminoxane. The reaction flask was connected to an ethylene long needle and a liquid seal, and ethylene gas was introduced (3 minutes) to exhaust the nitrogen in the flask, and the ethylene gas flow was turned down and the liquid seal was disconnected. A toluene (5.00mL) solution of bis[N-(3-tert-butyl salicylaldehyde) cyclopentylamine] zirconium dichloride (0.48g) was added, and the ethylene pressure was maintained at 0.1MPa. The reaction was continued until the color of the solution changed from yellow to white, and the ethylene gas was turned off, and the reaction was terminated. The polymer was acidified with ethanol for precipitation, washed, filtered and then vacuum dried for further experiments. The number average molecular weight M was measured by high temperature gel permeation chromatography (GPC). n =5,600 g / mol, M w / M n =2.6.
[0106] Using toluene as solvent, terminal hydroxyl polyethylene was synthesized by thiol-double bond click reaction. First, polyethylene (10 g, 1.8 mmol) was dissolved in toluene (219 g), and mercaptoethanol (2.79 g, 35.7 mmol) and azobisisobutyronitrile (0.9 g every 2 hours, a total of 2.7 g, 16.4 mmol) were added, and the reaction was allowed to proceed overnight at 100 ° C. After the reaction, the polymer was washed with methanol and filtered to obtain terminal hydroxyl polyethylene, which was then vacuum dried for further experiments. Polyethylene macroinitiator was synthesized by esterification reaction. The temperature of the esterification reaction in Example 1 (1) was increased from room temperature to 90 ° C, dry dichloromethane was replaced with dry toluene, and terminal hydroxyl hydrogenated polyisoprene was replaced with terminal hydroxyl polyethylene. The other steps were the same as the esterification reaction in Example 1 (1), and the polyethylene macroinitiator was prepared.
[0107] (2) Preparation of Polyethylene-b-polyglycidyl acrylate / polyglycidyl acrylate polyolefin-based nanoparticles
[0108] First, polyethylene macroinitiator (1.0000 g), ethyl α-bromophenyl acetate (0.0226 g), glycidyl acrylate (1.3224 g), cupric bromide (0.0020 g), tris(2-pyridylmethyl)amine (0.0053 g) and toluene (5.4189 g) were added to a 25 mL flask in sequence. After bubbling with nitrogen for 30 minutes, the flask was placed in an oil bath at 90 ° C for 15 minutes. Then, stannous octoate (0.0754 g) dissolved in toluene was added by syringe to initiate polymerization. The polymerization reaction lasted for 24 hours to form a dispersion of spherical nanoparticles, realizing the polymerization-induced self-assembly process, and the nanoparticles were precipitated in methanol three times for use.
[0109] (3) Preparation of 4-amino-2,2,6,6-tetramethylpiperidinyloxyl@(polyethylene-b-poly(glycidyl acrylate) / poly(glycidyl acrylate)) functionalized polyolefin-based nanoparticles
[0110] First, the nanoparticles prepared above (0.5000 g) were redispersed in toluene (10.60 mL, 9.50 g), and 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical (0.30 mL) was added. Then, after heating and refluxing at 90 ° C for 8 hours, 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical @ (polyethylene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles were prepared. Finally, the nanoparticles were precipitated in methanol three times to remove excess 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radicals.
[0111] Example 9
[0112] This example is the preparation of phosphoric acid@(polyethylene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles:
[0113] The 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical in Example 8 (3) is replaced with phosphoric acid, and the other steps are the same as Example 8, so as to prepare phosphoric acid@(polyethylene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles.
[0114] Example 10
[0115] This example is the preparation of N-phenyl-p-phenylenediamine@(polyethylene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles:
[0116] The 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical in Example 8 (3) is replaced with N-phenyl-p-phenylenediamine, and the other steps are the same as Example 8 to prepare N-phenyl-p-phenylenediamine@(polyethylene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles.
[0117] Embodiment 11
[0118] This example is the preparation of N-phenyl-p-phenylenediamine@(hydrogenated polycyclooctadiene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles:
[0119] (1) Preparation of hydrogenated polycyclooctadiene macroinitiator
[0120] Polycyclooctadiene with terminal double bonds was synthesized in dichloromethane by ring-opening metathesis polymerization. First, cyclooctadiene (3.0 g, 27.7 mmol) and anhydrous dichloromethane (68 mL) were added to a 200 mL flask. Under rapid stirring, a dichloromethane (9.58 mL) dilution of the second-generation Grubbs M204 catalyst (5.9 mg, 0.0069 mmol) was added to initiate the reaction. After 1 hour of reaction, a dichloromethane (2.00 mL) solution of 1-hexene (0.0233 g, 0.277 mmol) was added and the reaction was continued for 3 hours. At the end of the reaction, methanol was directly used to precipitate the polymer to retain the double bonds. After washing with methanol and filtering, the polymer was vacuum dried for further experiments. The number average molecular weight M was measured by gel permeation chromatography (GPC). n =51,000 g / mol, M w / M n =1.5.
[0121] The terminal hydroxyl polycyclooctadiene is synthesized by the thiol-double bond click reaction. The polyethylene in the thiol-double bond click reaction in Example 8 (1) is replaced by polycyclooctadiene, the amount of mercaptoethanol is reduced to 1 / 20 of the original, the temperature is reduced to 70°C, and the other steps are the same as in Example 8, to prepare the terminal hydroxyl polycyclooctadiene. The terminal hydroxyl hydrogenated cyclooctadiene is synthesized by hydrogenation reaction. The terminal hydroxyl polyisoprene in the hydrogenation reaction in Example 1 (1) is replaced by terminal hydroxyl polycyclooctadiene, and the other steps are the same as in the hydrogenation reaction in Example 1 (1), to prepare the terminal hydroxyl hydrogenated polycyclooctadiene. The hydrogenated polycyclooctadiene macroinitiator is synthesized by esterification reaction. The terminal hydroxyl hydrogenated polyisoprene in the esterification reaction in Example 1 (1) is replaced by terminal hydroxyl hydrogenated polycyclooctadiene, and the other steps are the same as in the esterification reaction in Example 1 (1), to prepare the hydrogenated polycyclooctadiene macroinitiator.
[0122] (2) Preparation of Hydrogenated Polycyclooctadiene-b-Poly(Glycidyl Acrylate) / Poly(Glycidyl Acrylate) Polyolefin-Based Nanoparticles
[0123] The hydrogenated polyisoprene macroinitiator in Example 1 (2) is replaced by a hydrogenated polycyclooctadiene macroinitiator (1.000 g), glycidyl methacrylate is replaced by glycidyl acrylate (1.3224 g), the amount of ethyl 2-bromo-2-methylpropionate is increased by 1 time, the amount of copper bromide is increased by 1 time, the amount of tri[2-(dimethylamino)ethyl]amine is increased by 1 time, the amount of cyclohexane is increased by 1 time, and the amount of stannous octoate is increased by 1 time. The other steps are the same as those in Example 1 (2), and hydrogenated polycyclooctadiene-b-polyglycidyl acrylate / polyglycidyl acrylate polyolefin-based nanoparticles can be prepared.
[0124] (3) Preparation of polyolefin-based nanoparticles functionalized with N-phenyl-p-phenylenediamine@(hydrogenated polycyclooctadiene-b-poly(glycidyl acrylate) / poly(glycidyl acrylate)
[0125] First, the nanoparticles prepared above (0.5000 g) were redispersed in tetrahydrofuran (10.6 mL, 9.5 g), and N-phenyl-p-phenylenediamine (0.90 mL) was added. Then, after reacting at 40° C. for 24 hours, N-phenyl-p-phenylenediamine@(hydrogenated polycyclooctadiene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles were prepared. Finally, the nanoparticles were precipitated in methanol three times to remove excess N-phenyl-p-phenylenediamine.
[0126] Example 12
[0127] This example is the preparation of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid@(hydrogenated polycyclooctadiene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles
[0128] The N-phenyl-p-phenylenediamine in Example 11 (3) is replaced with 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid, the reaction temperature is increased to 90° C., the reaction time is adjusted to 8 hours of heating reflux, and the other steps are the same as Example 11, so as to prepare 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid@(hydrogenated polycyclooctadiene-b-poly(glycidyl acrylate) / poly(glycidyl acrylate) functionalized polyolefin-based nanoparticles.
[0129] Embodiment 13
[0130] This example is the preparation of 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical @ (hydrogenated polycyclooctadiene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles
[0131] The N-phenyl-p-phenylenediamine in Example 11 (3) is replaced with 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical, the reaction temperature is increased to 90° C., the reaction time is adjusted to 8 hours of heating reflux, and the other steps are the same as Example 11, so as to prepare 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical @ (hydrogenated polycyclooctadiene-b-poly(glycidyl acrylate) / poly(glycidyl acrylate) functionalized polyolefin-based nanoparticles.
[0132] Test Example 1
[0133] This test example is a flame retardant test of phosphoric acid @ (hydrogenated polyisoprene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate)) functionalized polyolefin-based nanoparticles prepared in Example 1:
[0134] As described in Example 1, the nanoparticles are spherical in structure, and the average diameter thereof is about 341 nm as measured by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The phosphoric acid is successfully introduced by thermogravimetric analysis (TGA), and further characterized and confirmed by field emission scanning electron microscopy (FESEM) and energy dispersive X-ray spectrometer (EDS). It can be clearly observed from the EDS graph that the oxygen (O) element and the phosphorus (P) element have been successfully introduced into the nanoparticles.
[0135] Subsequently, the flame retardant properties of the nanoparticles were studied by a microcalorimeter (MCC). About 5.0 mg of the sample was rapidly heated to 750°C at a heating rate of 1°C / s in a nitrogen atmosphere of 80 cc / min. The pyrolysis products in the nitrogen flow were carried into the combustion chamber (20% O2 and 80% N2) by a 20 cc / min air flow and burned at a temperature of 900°C. Figure 3 As shown in the figure, after the introduction of phosphoric acid into the PGMA core, the heat release rate (HRR) of the sample was reduced. Based on the curve measured by MCC, the total heat release (THR), heat release capacity (HRC) and peak heat release rate (pHRR) of the sample can be obtained, which are all reduced to varying degrees compared with before the introduction of phosphoric acid, proving that the introduction of phosphoric acid effectively improves the flame retardancy of the nanoparticles.
[0136] Test Example 2
[0137] This test example is a flame retardant test of phosphoric acid @ (hydrogenated polyisoprene-b-poly(glycidyl methacrylate)) functionalized polyolefin-based nanoparticles prepared in Example 2:
[0138] The phosphoric acid@(hydrogenated polyisoprene-b-polyglycidyl methacrylate / polyglycidyl methacrylate) functionalized polyolefin-based nanoparticles in Test Example 1 were replaced with phosphoric acid@(hydrogenated polyisoprene-b-polyglycidyl methacrylate) functionalized polyolefin-based nanoparticles. The phosphoric acid content in the sample increased with the increase of polyglycidyl methacrylate content, and its MCC curve is as follows: Figure 4 As shown, the heat release rate (HRR), total heat release (THR), heat release capacity (HRC) and peak heat release rate (pHRR) of the samples were significantly reduced, proving that the introduction of higher content of phosphoric acid can effectively improve the flame retardancy of nanoparticles.
[0139] Test Example 3
[0140] This test example is a flame retardant test of phosphoric acid @ (hydrogenated polybutadiene-b-poly(glycidyl methacrylate) / poly(glycidyl methacrylate)) functionalized polyolefin-based nanoparticles prepared in Example 5:
[0141] The phosphoric acid@(hydrogenated polyisoprene-b-polyglycidyl methacrylate / polyglycidyl methacrylate) functionalized polyolefin-based nanoparticles in Test Example 1 were replaced with phosphoric acid@(hydrogenated polybutadiene-b-polyglycidyl methacrylate / polyglycidyl methacrylate) functionalized polyolefin-based nanoparticles, and the results were similar to those in Test Example 1, which can prove the successful introduction of phosphoric acid and the effective improvement of the flame retardancy of the nanoparticles.
[0142] Test Example 4
[0143] This test example is a flame retardant test of phosphoric acid @ (polyethylene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles prepared in Example 9:
[0144] The phosphoric acid@(hydrogenated polyisoprene-b-polyglycidyl methacrylate / polyglycidyl methacrylate) functionalized polyolefin-based nanoparticles in Test Example 1 were replaced with phosphoric acid@(polyethylene-b-polyglycidyl acrylate / polyglycidyl acrylate) functionalized polyolefin-based nanoparticles, and the results were similar to those in Test Example 1, which can prove the successful introduction of phosphoric acid and the effective improvement of the flame retardancy of the nanoparticles.
[0145] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A functionalized polyolefin-based nanoparticle, characterized in that: The nanoparticles are of a core-shell structure, wherein the core layer is a polymer containing functional groups and the shell layer is a polyolefin chain with a stabilizing effect.
2. The functionalized polyolefin-based nanoparticle according to claim 1, characterized in that: The polymer containing functional groups is a polymer chain containing epoxy groups that is post-modified with functional groups; The functional groups include one or more combinations of phosphate, hindered amine, hindered phenol and 2,2,6,6-tetramethylpiperidinyl oxide.
3. The functionalized polyolefin-based nanoparticle according to claim 1, characterized in that: The polyolefin chain includes one or more combinations of hydrogenated polydienes, hydrogenated polycycloolefins, polyisobutylene, polyethylene and polypropylene.
4. A method for preparing functionalized polyolefin-based nanoparticles according to any one of claims 1 to 3, characterized in that: The steps include: S1: Polyolefin-based macromolecular initiator, small molecule initiator, epoxy group-containing monomer and catalyst are subjected to atom transfer radical polymerization-mediated polymerization-induced self-assembly in a solvent to prepare a nanoparticle precursor having a core layer of epoxy group-containing polymer chains and a shell layer of a stabilizing polyolefin chain; S2: adding a functional additive to the nanoparticle precursor obtained in step S1, and reacting to obtain functionalized polyolefin-based nanoparticles having a core layer of a polymer containing functional groups and a shell layer of a polyolefin chain having a stabilizing effect.
5. The method for preparing functionalized polyolefin-based nanoparticles according to claim 4, characterized in that: The polyolefin-based macroinitiator is prepared by the following steps: SS1: Preparation of hydroxyl-terminated precursors by controlled polymerization and end-capping of olefin monomers, and preparation of hydroxyl-terminated polyolefin polymers by hydrogenation; SS2: The hydroxy-terminated polyolefin polymer obtained in step SS1 is subjected to an esterification reaction with a bromine-containing small molecule reagent to obtain a polyolefin-based macromolecular initiator containing terminal bromine.
6. The method for preparing functionalized polyolefin-based nanoparticles according to claim 5, characterized in that: Step SS1 includes one or both of the following: i) the controlled polymerization comprises one or more combinations of anionic polymerization, coordination polymerization and ring-opening metathesis polymerization; ii) The catalyst for the hydrogenation reaction comprises a combination of one or more of p-toluenesulfonyl hydrazide, lead / barium sulfate, nickel / aluminum catalyst and platinum / rhenium catalyst.
7. The method for preparing functionalized polyolefin-based nanoparticles according to claim 5, characterized in that: In step SS2, the bromine-containing small molecule reagent includes one or a combination of 2-bromoisobutyryl bromide and α-bromophenylacetic acid.
8. The method for preparing functionalized polyolefin-based nanoparticles according to claim 4, characterized in that: Step S1 includes one or more of the following: i) the small molecule initiator comprises one or a combination of ethyl 2-bromo-2-methylpropionate and ethyl α-bromophenylacetate; ii) the catalyst comprises one or more combinations of cupric bromide / tris(2-dimethylaminoethyl)amine / stannous octoate, cupric bromide / N,N,N',N",N"-pentamethyldiethylenetriamine, cupric bromide / tris(2-dimethylaminoethyl)amine / azobisisobutyronitrile and cupric bromide / tris(2-pyridylmethyl)amine / stannous octoate; iii) the epoxy group-containing monomer comprises one or a combination of glycidyl methacrylate and glycidyl acrylate; iv) the solvent is a good solvent for the polyolefin-based macromolecular initiator and a poor solvent for the polymer chain containing epoxy groups; v) The reaction temperature of the atom transfer free radical polymerization-mediated polymerization-induced self-assembly is 25-150° C., the reaction time is 0.5-48 hours, and the solid content of the reaction system is 0.1-30%.
9. The method for preparing functionalized polyolefin-based nanoparticles according to claim 4, characterized in that: In step S2, the functional auxiliary agent includes one or more combinations of phosphoric acid, phosphorus oxychloride, N-phenyl-p-phenylenediamine, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid and 4-amino-2,2,6,6-tetramethylpiperidinyloxy free radical.
10. Use of the functionalized polyolefin-based nanoparticles according to any one of claims 1 to 3 in the field of flame retardants and antioxidants.
Citation Information
Patent Citations
Multi-component surfacing organic-inorganic composite nanoparticle as well as preparation method and application thereof
CN113736207A
Zwitterionic polymer-based organic-inorganic composite nanoparticles as well as preparation method and application thereof
CN118406221A
Polymer nano-particle with polar core and method for manufacturing same
US20060173130A1